PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KEPUASAN JAMAAH HAJI PADA KEMENTERIAN AGAMA KOTA BENGKULU - Juwairiah, Juwairiah; Idwal, Idwal; Muttaqin, Faisal (ITB AAS Indonesia Surakarta, 2024)
This research aims to determine whether there is a significant influence of total quality management on the satisfaction of Hajj pilgrims at the Ministry of Religion, Bengkulu Watuk City. To test this, the researcher used a quantitative descriptive method with a sample of 30 respondents. The data analysis technique used is simple linear regression using SPSS. From the results of the research and discussion, it was found that total quality management does not have a significant influence on the satisfaction of Hajj pilgrims from the Ministry of Religion of Bengkulu City.